Une « éthique du paysage » est-elle souhaitable ? - Anne Sgard (VertigO)
“The landscape is indissolubly, as any public space, a political and sensitive question” writes J.M. Besse. Landscape doesn’t amount any more to natural or pastoral sites, codified and recommended in guides, it has conquered the ordinary environment, the everyday life; landscape is changing, constantly modified according to our way of seeing. This landscape, as political object, belongs to all, everyone is entitled to glance and everyone intervenes on the materiality of our common landscape. The impossibility to identify standards applicable to the landscape has been pointed out: who has legitimacy to say what the landscape ought to be? From then on, we observe recurring calls for ethics.Is an "ethics of the landscape" to be hoped? Ethics seems essential as far as the definition of the debate on the common determines who is entitled to take part; without ethical demand the landscape can serve withdrawal, exclusion and segregation. Ethics cannot consist in standards of intervention; it may concern the field of the participation and the collective debate on what we have in common, for whom we are responsible and what we want to pass on. Beyond the consensual landscape, the showcase for political projects, the landscape can turn out to be disturbing when we ask the question “for whom?”